E-Mental Health: An investigation of requirement policies and organizational governance for National Health Information System in Indonesia - Rohajawati, Siti; Pamungkas, Bani; Rey Fatri, Refyul; Saragih, Hoga (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to investigate the needs of policies and organizational governance for the National Health Information System in Indonesia (SIKNAS). Data were collected using a survey, observation, and in-depth interview with the representative stakeholders. The results have been confirmed and validated through focus group discussions at two provincial governments. The study found that there were gaps in policies and organizational governance at central and regional levels. The implications of research will raise awareness about the importance of information and knowledge to support the government in improving the quality of mental health services. In addition, it can also improve health services knowledge for the community and increase research interest in developing an e-mental health and knowledge management system (KMS).